The gut microbiota: A new perspective for tertiary prevention of hepatobiliary and gallbladder diseases - Huang, Xiaoyu; Yang, Yi; Li, Xueli; Zhu, Xiaoya; Lin, Dan; Ma, Yueran; Zhou, Min; Cui, Xiangyi; Zhang, Bingyu; Dang, Dongmei; Lü, Yuhong; Yue, Changwu (Frontiers in Nutrition, 2023)
The gut microbiota is a complex ecosystem that has coevolved with the human body for hundreds of millions of years. In the past 30 years, with the progress of gene sequencing and omics technology, the research related to gut microbiota has developed rapidly especially in the field of digestive system diseases and systemic metabolic diseases. The common bile duct starts from the liver and communicates with the gallbladder and eventually drains into the duodenal papilla together with the main pancreatic duct of the pancreas. Over 70% of the blood supply to the liver comes from the portal vein. Bile is synthesized by the liver and concentrated by the gallbladder and enters the intestine to function with digestive enzymes secreted by the pancreas. The liver, gallbladder, and pancreas may be exposed to intestinal flora if the intestinal barrier is damaged or the microbiota is dysregulated. The bile acids that enter the intestine affect the abundance of intestinal flora, and its synthesis is regulated by intestinal flora. A small amount of bile acids that is not reabsorbed needs to be chemically modified with the help of intestinal flora. Mechanical, biological, immune, and other factors make the intestinal flora form a close bidirectional connection with the liver, gallbladder, and pancreas, which can be called the “gut–liver–biliary–pancreatic axis”. The recent progress in the direction of intestinal flora has proven its remarkable potential clinical application on liver, gallbladder, and pancreas principal diseases. This review summarizes the role of intestinal microbiota in the pathogenesis and biotherapies based on liver, gallbladder, and pancreas principal diseases.